2017
DOI: 10.1001/jamainternmed.2016.8467
|View full text |Cite
|
Sign up to set email alerts
|

Financial Conflicts of Interest Among Hematologist-Oncologists on Twitter

Abstract: Twitter, the social media service that permits 140-character posts or "tweets," is undergoing rapid uptake by physicians. 1 Twitter allows physicians to communicate, interpret, highlight, and curate information as well as engage in discussion or debate with other physicians, patients, patient advocates, researchers, investors, and industry employees. More than 60% of tweets authored by medical professionals in the United States are health-related, and approximately 14% mention commercial products or services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 3 publications
3
31
0
Order By: Relevance
“…While our study is the first to examine FCOIs of emergency medicine contributors on social media, it does not directly address the impact of FCOI on the content of these posts. However, a study similar to ours of United States–based hematologists‐oncologist on Twitter revealed that approximately 80% who use Twitter have an FCOI with a median nonresearch general payment of over $1,600 . Of those with an FCOI of at least $1,000, 81% mentioned a drug from a company where they have a FCOI, and tweets about conflicted drugs were more “positive” compared to tweets about nonconflicted drugs .…”
Section: Characteristics Of Selected Authors From 31 Foamed Websites supporting
confidence: 61%
See 1 more Smart Citation
“…While our study is the first to examine FCOIs of emergency medicine contributors on social media, it does not directly address the impact of FCOI on the content of these posts. However, a study similar to ours of United States–based hematologists‐oncologist on Twitter revealed that approximately 80% who use Twitter have an FCOI with a median nonresearch general payment of over $1,600 . Of those with an FCOI of at least $1,000, 81% mentioned a drug from a company where they have a FCOI, and tweets about conflicted drugs were more “positive” compared to tweets about nonconflicted drugs .…”
Section: Characteristics Of Selected Authors From 31 Foamed Websites supporting
confidence: 61%
“…Based on the current specialty guidelines for FCOI discovery and our investigation findings, we recommend that all FOAMed contributors explicitly declare FCOIs on FOAMed content—or use #FCOI on Twitter—or provide a link to their OPD profile. In this study of emergency medicine FOAMed websites and blogs, we discovered that 15% of FOAMed contributors had FCOIs in 2017 in the OPD compared to 25% of all emergency physicians with FCOIs in 2015 .…”
Section: Characteristics Of Selected Authors From 31 Foamed Websites mentioning
confidence: 99%
“…As a result, it has been argued that pharmaceutical companies can engage health providers to hype drugs, strategically promoting some medicines, as well as stressing the positive achievements of clinical trials. In a report by Kaestner et al , almost 80% of haematologists–oncologists on Twitter had some COIs with companies 15 16. Interestingly, 80% among the most active haematologists on Twitter mentioned at least one drug from a company for which a financial COI was disclosed elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…However, when Tao et al evaluated the Twitter accounts of US-based hematologist – oncologists, they found that 79.5% had some form of financial conflict of interest (COI) [36]. DeCamp described some potential dangers of undisclosed physician COI including bias in clinical trial recruitment, as well as implications for trainee, medical student, and patient education [37].…”
Section: Benefitsmentioning
confidence: 99%